Physical and mechanical characteristic of particleboards produced with residues of sugarcane and stem leaves of bamboo bonded with castor oil adhesive - Bezerra, Barbara Stolte; Valarelli, Ivaldo De Domenico; Battistelle, Rosane Aparecida Gomes [UNESP]; Zuim, Aline de Lima; Chahud, Eduardo; Christoforo, André L.; Lahr, Francisco Antonio Rocco (Trans Tech Publications, 2015)
In this research the aim was produce a particleboard with alternative materials and evaluated its physical and mechanical characteristics. The raw materials used are residues from sucarcane bagasse (SC) (Saccharum officinarum) and stem leaves of bamboo (B) (Dendrocalamus giganteus), bonded with a bi component adhesive based on castor oil. It was produced particleboards with five different traces: 100% SC, 75% SC+25% B, 50% SC+50% B, 25% SC +75%B and 100 % B. Their physical and mechanical characteristics were evaluated accordingly to Brazilian standard NBR 14810-3. Regarding the results obtained, it can be detached that for physical and mechanical evaluation it is evident a negative relation among the amount the sugarcane bagasse and their physical and mechanical characteristics, that is particleboards with low concentrations of sugarcane bagasse had better results. However all particleboards could be recommended for use as sealing particleboards in the segment of civil construction.
Keywords: Bamboo; Particleboard; Stem leaves; Sugarcane residues